ROBOTIKA SEBAGAI PILAR PENGEMBANGAN SIKAP SISWA PADA ERA DIGITAL DI SD MUHAMMADIYAH 9 MALANGROBOTIKA SEBAGAI PILAR PENGEMBANGAN SIKAP SISWA PADA ERA DIGITAL DI SD MUHAMMADIYAH 9 MALANG: Penelitian deskriptif - Febriantika, Novi; Wahyu Putri Utami, Ima; Galuh Danawati, Murtyas (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Robotics is a branch of science and technology that involves the design, construction, operation, and use of robots. This study aims to describe the implementation of the robotics program at SD Muhammadiyah 9 Malang. The research employs a qualitative descriptive method. Data sources for this study include information from the school principal, student affairs, and robotics teachers. Data collection methods used are observations, interviews, and documentation. The data analysis techniques applied are data reduction, data presentation, and conclusion drawing. The results indicate that the implementation of the robotics program successfully enhances not only students' technical skills but also their attitudes. The robotics program at SD Muhammadiyah 9 Malang has been effectively executed, from planning to implementation and assessment. Supporting factors for the program include available facilities and infrastructure, collaboration with skilled trainers, strong support from the school, and high interest from students and parents. However, obstacles include noisy classroom conditions, the absence of teachers with specialized skills in robotics, concerns about the high costs of equipment, and the perception of some that robotics is merely a form of play